THE MODEL OF CORRUPTION COURT IN THE ARCHIPELAGO PROVINCE WITH LOW COSTS, QUICK, AND SIMPLE PROCESS OF IMPLEMENTATION - Sulistyanta, Sulistyanta; Sinurat, Aksi; Effendi, Jauhari; Putri, Fatma Ayu Jati (Yustisia, 2017)
The enactment of Law Number 46 of 2009 about Corruption Court, is authorized to examine and decide the crime of corruption cases proposedby KPK or Prosecutor (State and High). Based on Article 35 paragraph (1) jo paragraph (4) of Law Number 46 of 2009, confirmed that corruption courts (TIPIKOR courts) are only located in each provincial capital whose jurisdiction covers the province concerned. By this provision, the Prosecutor Office in each district/city must transfer the corruption cases to the Corruption Court in the provincial capital. There are the problems as the following: first one, Is the process of criminal justice in the archipelago province like East Nusa Tenggara (NTT) able to fulfill the judicial principle of quick, low cost and simple?; second one, Is this condition not an obstacle in the process of criminal law enforcement in NTT?; The result of this research is that the Corruption Court in Kupang, conducted by several Prosecutor Offices, the samples do not meet the judicial principles of quick, low costs and simple. The obstacles besides spending much expenses, there are other factors such as weather, intentionally neglect the obligation as the experts, witnesses due to long time and high expenses.  Law enforcement becomes less maximal due to the existing budget, and it can only be done by a minimal law enforcement process with a fairly expensive cost.